How to solve 5(3-x)+1=)3(x4)?

Welcome to my article 5(3-x)+1=)3(x4) This question is taken from the simplification lesson.
The solution of this question has been explained in a very simple way by a well-known teacher by doing addition, subtraction, and fractions.
For complete information on how to solve this question 5(3-x)+1=)3(x4) read and understand it carefully till the end.

Let us know how to solve this question 5(3-x)+1=)3(x4).

First write the question on the page of the notebook

5(3-x)+1=)3(x4)

Let us first solve the question.

\displaystyle 5\text{x3-5x}x+1=3\text{x}x+4\text{x}3

\displaystyle 15-5x+1=3x+12

put the variable amount together and the constant amount together

\displaystyle 15+1-12=3x+5x

\displaystyle 16-12=8x

\displaystyle 8x=16-12

\displaystyle 8x=4

\displaystyle x=\frac{4}{8}

The numerator and denominator of 4 \displaystyle x=\frac{1}{2}

So the absolute solution of this article 5(3-x)+1=)3(x4) is \displaystyle x=\frac{1}{2} .

See other similar examples.

Example no 1.

8(2-x)-6=6(x+1)+2+9x

Let’s know the solution of this article.——

8(2-x)-6=6(x+1)+2+9x

The first one is on Costak.

\displaystyle 8\text{x}2-8\text{x}x-6=6x\text{x+6x1+2+9x}

\displaystyle 16-8x-6=6x+6+2+9x

Putting the variable amount together and the constant amount together.

\displaystyle 16-6-6-2=6x+9x+8x

\displaystyle 16-14=23x

\displaystyle 2=23x

\displaystyle \frac{2}{{23}}=x

or \displaystyle x=\frac{2}{{23}}

Hence the assertion of this article is 2/23.

Example no 2.

7(6x)+2(5+x)=(8x+1)+2(2(8=x)

Let’s know the solution of this article.——

\displaystyle 7(6+x)+2(5=x)=(8x=1)+2(8+x)

In the given article, let us first solve the cost.

\displaystyle 7\text{x}6+7\text{x}x+2\text{x}5+2\text{x}x=8x+1+2\text{x8+2x}x

\displaystyle 42+7x+10+2x+=8x=1=16+2x

After this, by keeping the variable amount together and the constant amount together, we solve it by doing addition and subtraction.

\displaystyle 47+10-1-16=-7x-2x+8x+2x

Now let’s solve the + sign together and the – sign together.

57-17=-9x=10x

Since – and – are joined together.

See also  How to solve 2/3+5x/5+12/3

So the absolute solution of this article 7(6+x )+2 (5+x)=(8x+1 )+2 (8+2) is 40.

How to solve 5(3-x)+1=)3(x4)? This article has been completely solved by tireless effort from our side, still if any error remains in it then definitely write us your opinion in the comment box. If you like or understand the methods of solving all the questions in this article, then send it to your friends who are in need.

Note: If you have any such question, then definitely send it by writing in our comment box to get the answer.
Your question will be answered from our side.

Thank you once again from our side for reading or understanding this article completely.

Leave a Comment